IMMUNE REGULATORY MECHANISMS OF THE RESPIRATORY MUCOSA - SWIRSKI, KRZYSZTOF FILIP (My University, 2004)
Asthma and other allied allergic diseases represent a significant burden to health care and are recognized as endemic in the Western World. While a diverse array of effective pharmacopoeia provides reprieve from symptoms, no preventive or curative therapies are currently available. This is in part due to the paucity of understanding how allergic diseases develop. Recently, remarkable progress has been made in this regard, largely due to the discovery of regulatory mechanisms that control responsiveness to antigen in the airway. Indeed, to understand fully why people develop asthma requires an understanding of both allergic sensitization and tolerance. Work presented in this thesis contributes to our knowledge of inhalation tolerance. Using a classical mouse model of allergic airways inflammation, we show in Chapter 2 that inhalation tolerance is a persistent and active process as it prevents the generation of airway eosinophilia, antigenspecific IgE and airway hyperresponsiveness upon secondary immunogenic challenge, independently of IL-lO or IFN-y. Building on these observations, in Chapter 3 we show in a mucosal model of allergic sensitization that inhalation tolerance cannot be broken with the expression of GM-CSF, a potent growth factor and cytokine that has been associated with asthma and allergy in both human and animal subjects. However, concomitant expression of decorin, a natural inhibitor of TGF-f3, reverses inhalation tolerance, thus implicating TGF-f3 as putatively important in regulating responsiveness in the airway. In Chapter 4, we identify an alternative mode of tolerance. We show that chronic exposure to innocuous antigen in sensitized mice does not lead to chronic inflammation but to abrogated eosinophilia that can, nevertheless, be reversed with the expression of GM-CSF. Collectively, these findings enrich our understanding of tolerance and provide a framework for new discoveries that may, ultimately, lead to novel and powerful therapies for allergic disease.
Keywords: Medical Sciences; Medical Sciences